PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH STRES KERJA TERHADAP KOMITMEN ORGANISASIONAL PADA KARYAWAN - Budiman, I Made Gilang; Supartha, I Wayan Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.11.TAHUN.2023, 2023)
The purpose of this study was to analyze the effect of job stress on job satisfaction, to analyze the effect of job satisfaction on organizational commitment, to analyze the effect of job stress on organizational commitment to analyze job satisfaction in mediating the effect of job stress on commitment. This research was conducted at PT. Atika Mandiri. The number of samples used in this study were 62 employees, using the saturated sample method (census), which used the entire population as a sample. Collecting data using questionnaires and interviews. The data were analyzed using path analysis techniques (Path Analysis). In this study, the theory used is social exchange theory. The results showed that job stress had a negative and significant effect on job satisfaction. PT. Atika Mandiri, job satisfaction has a positive and significant effect on organizational commitment, job stress has a negative and significant effect on organizational commitment, and job satisfaction mediates the effect of job stress on organizational commitment at PT. Atika Mandiri. This research can provide evidence on the development of human resource management science that is able to explain the theoretical model used as a basis in formulating the hypothesis.